2016
DOI: 10.1007/s00296-016-3550-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA-31 and microRNA-21 as regulatory biomarkers in the activation of T lymphocytes of Egyptian lupus patients

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by familial aggregation and genetic predisposition. MicroRNAs (MiRNAs) serve as critical biomarkers in lupus patients because of their aberrant expression in different SLE stages. The study aimed to investigate the correlation of miR-31 and miR-21 with IL-2 in SLE patients as regulatory biomarkers in the activation of T lymphocytes of Egyptian lupus patients. Quantitative RT-PCR is carried out to estimate the expressions of miR-31 and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, five articles were excluded by reading their complete articles due to article types, seven studies lacked available data to construct a 2×2 table, and four articles lacked a comparison between SLE patients and healthy controls. Finally, 17 studies [17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The process of study selection was illustrated in Fig 1. Except the study of Zununi Vahed et al [42] is a cross-sectional trial, all others are prospective trials.…”
Section: Search Resultsmentioning
confidence: 99%
“…In 2011, Stagaki et al [16] suggested that miRNA-21 (miR-21) was a potential biomarker for SLE. Since then, a series of studies [17][18][19][20][21] have also verified the role of miR-21 in SLE. In addition, these studies [18][19][20][21] have found other miRNAs (miR-155, -181a, -196a, -31, and -148a) dysregulated in SLE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, miR‐31 plays an important role in the immune system. For instance, overexpression of miR‐31 influences the activation of T lymphocytes and inflammatory reactions via upregulation of interleukin‐2 (IL‐2) expression . Recently, there has been increasing attention on the role of miR‐31 in the development of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, overexpression of miR-31 influences the activation of T lymphocytes and inflammatory reactions via upregulation of interleukin-2 (IL-2) expression. [8][9][10] Recently, there has been increasing attention on the role of miR-31 in the development of psoriasis. Some studies have reported that miR-31 is overexpressed in proliferating KCs in lesions of patients with psoriasis.…”
Section: Introductionmentioning
confidence: 99%